2021
DOI: 10.3389/fpsyg.2021.677575
|View full text |Cite
|
Sign up to set email alerts
|

Parental Reports of Preschoolers' Lexical and Syntactic Development: Validation of the CDI-III for European Portuguese

Abstract: This study presents the validation analysis of the European Portuguese version of the MacArthur-Bates Communicative Development Inventory III (CDI-III-PT). The CDI-III-PT is a parental report measure allowing researchers to assess expressive vocabulary and the syntactic abilities of children aged 2;6–4;0. In this study, we present a version comprising a lexical subscale which follows the Swedish adaptation and an original syntactic subscale allowing us to include language-specific structures. The reports of 73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 60 publications
2
18
0
2
Order By: Relevance
“…Odeskog and Stenberg (2015) tested the validity of the Swedish form in a sample of 41 typically developing children aged 3;0-3;11 and found low correlations of the Vocabulary section with the Peabody Picture Vocabulary Test (r = 0.324) and the Boston Naming Test (r = 0.368). Cadime et al (2021) reported that the Vocabulary total score and the Syntax score of the European Portuguese CDI-III showed moderate correlations with the language score of the Griffiths Mental Development Scales (r = 0.486* and r = 0.445*, respectively) in a small sample of 23 typically developing children aged 30-48 months.…”
Section: Adaptationsmentioning
confidence: 95%
See 3 more Smart Citations
“…Odeskog and Stenberg (2015) tested the validity of the Swedish form in a sample of 41 typically developing children aged 3;0-3;11 and found low correlations of the Vocabulary section with the Peabody Picture Vocabulary Test (r = 0.324) and the Boston Naming Test (r = 0.368). Cadime et al (2021) reported that the Vocabulary total score and the Syntax score of the European Portuguese CDI-III showed moderate correlations with the language score of the Griffiths Mental Development Scales (r = 0.486* and r = 0.445*, respectively) in a small sample of 23 typically developing children aged 30-48 months.…”
Section: Adaptationsmentioning
confidence: 95%
“…Items in the vocabulary section have been revised and sections for measuring metalinguistic awareness and pronunciation accuracy have been added (Eriksson, 2017 ). The Swedish form served as the basis of the recent Estonian adaptation put forward by Tulviste and Schults ( 2020 ) and the structure of the Swedish CDI‐III vocabulary section were also used in the recent development of the CDI‐III for European Portuguese along with carefully adapted sections for syntax for each language based on earlier CDI‐WS forms and spontaneous language samples (Cadime et al., 2021 ). Studies of validity and classification accuracy have also been conducted and published for some of the adaptations with largely successful results.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Há já muita investigação que mostra que variáveis sociodemográficas e socioeconómicas, incluindo o nível de instrução dos pais, e da mãe em particular, são determinantes no desenvolvimento do vocabulário da criança a partir dos 2 anos de idade: crianças de meios socioeconómicos mais favorecidos e cujas mães têm níveis altos de escolarização possuem um vocabulário mais vasto (Cadime et al, 2018). A importância destas variáveis no desenvolvimento sintático não é tão clara, mas há já investigação que mostra que o desenvolvimento sintático também é afetado por estas variáveis: crianças cujas mães têm um nível de instrução mais alto produzem estruturas sintáticas mais complexas e mais diversificadas (Cadime et al, 2021). Há, ainda assim, muitas questões que permanecem em aberto no que diz respeito ao papel do input no desenvolvimento sintático.…”
Section: Aquisição Da Sintaxe Da L1: Grandes Questõesunclassified